(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2024)
The importance of predicting accident rates lies in the improvement of road infrastructure and the effective implementation of laws and traffic regulations. The statistical change of many phenomena over time is described by time series. This paper aims to forecast the number of individuals involved in road accidents in Albania by applying SARIMA model approach. This study used monthly number of individuals involved in road traffic accidents in Albania from 2016 to 2023. Using forecasting techniques for the number of traffic accidents can serve as a valuable strategy for achieving various objectives including the implementation of traffic safety campaigns, strategies, and action plans outlined in traffic safety initiatives. The model was found to be effective in capturing the underlying patterns and trends in the data, providing valuable insights for understanding and forecasting traffic accident occurrences in Albania.